Composition, adhesive composition, adhesive structure, and method for producing adhesive structure
Patent Information
- Application Number
- JP2023142034
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-13
AI Technical Summary
【0011】 本発明によれば、無機部材同士が接着された接着構造体を加工搬送した場合にも、接着構造体の剥離を抑制できる組成物や接着性組成物、ならびに、その組成物や接着性組成物を用いた接着構造体および接着構造体の製造方法を提供することができる。
Smart Images

Figure 2025035169000001 
Figure 2025035169000002 
Figure 2025035169000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a composition, for example, an adhesive composition, an adhesive structure, and a method for producing an adhesive structure. [Background technology]
[0002] Patent Documents 1 to 3, for example, describe techniques relating to adhesives for bonding inorganic members such as metals together.
[0003] Patent Document 1 discloses a two-component acrylic adhesive composition comprising (1) a polymerizable monomer having a (meth)acryloyl group, (2) a polymerization initiator, (3) a reducing agent, (4) a polymer containing polyorganosiloxane and polyalkyl (meth)acrylate, and (5) an elastomer soluble in the (meth)acrylic acid ester monomer, wherein the polymer containing polyorganosiloxane and polyalkyl (meth)acrylate is capable of swelling with the polymerizable monomer having a (meth)acryloyl group. The document describes that the two-component acrylic adhesive composition can be quickly cured at room temperature to fix components in a short time, and that even in this case, the adhesive strength is excellent, making it possible to quickly produce a bonded body with excellent adhesive strength.
[0004] Patent Document 2 discloses a curable resin composition containing, relative to 100 parts by mass of (A) (meth)acrylate monomer, 1 to 50 parts by mass of (B) elastomer, 1 to 50 parts by mass of (C) bismaleimide compound, 1 to 50 parts by mass of (D) poly(meth)acrylate having one or more radically polymerizable functional groups per molecule, 5 to 100 parts by mass of (E) compound containing an alkylene oxide chain and having two or more radically polymerizable functional groups per molecule, 0.1 to 10 parts by mass of (F) polymerization initiator, and 0.01 to 10 parts by mass of (G) curing accelerator. It is described that the curable resin composition exhibits both high shear adhesive strength and peel adhesive strength even after heat exposure, and has excellent adhesion to adherends.
[0005] Patent Document 3 discloses an adhesive set comprising a first liquid containing a polymerization initiator and a second liquid containing a reducing agent, wherein at least one of the first liquid and the second liquid further contains (meth)acryloylmorpholine as a monomer, and describes that the adhesive set has excellent rapid curing properties at room temperature, and a method for manufacturing a structure using the adhesive set is provided. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Publication No. 2020-026507 [Patent Document 2] Japanese Patent Application Publication No. 2018-172565 [Patent Document 3] Patent Publication No. 2021-024910 Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention provides a composition and adhesive composition that can suppress peeling of a bonded structure in which inorganic members are bonded together, even when the bonded structure is processed and transported, as well as a bonded structure and a method for manufacturing a bonded structure that use the composition or adhesive composition. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to achieve the above object, and as a result, have found that a two-part adhesive composition containing a radical polymerizable monomer (A), a polymerization initiator (B), and a reducing agent (C), wherein the first part contains the radical polymerizable monomer (A) and the polymerization initiator (B) and the second part contains the radical polymerizable monomer (A) and the reducing agent (C), and the tensile shear strength T(1) is set to 0.01 MPa or more, can suppress peeling of the bonded structure even when the bonded structure in which inorganic members are bonded to each other is processed and transported, thereby completing the present invention.
[0009] According to the present invention, there are provided a composition, an adhesive composition, an adhesive structure, and a method for producing an adhesive structure, as shown below.
[0010] [1] A two-component adhesive composition comprising: A method for producing a polymerization reaction system comprising: a radical polymerizable monomer (A); a polymerization initiator (B); and a reducing agent (C); the first agent contains the radical polymerizable monomer (A) and the polymerization initiator (B), the second agent contains the radical polymerizable monomer (A) and the reducing agent (C), An adhesive composition having a tensile shear strength T(1) of 0.01 MPa or more, measured according to the <Tensile Shear Strength> below. <Tensile shear strength> A 20 mm area from the edge of a 25 mm wide, 100 mm long, and 1.6 mm thick cold-rolled steel plate (JIS G 3141:2017, SPCC-SD) was sandblasted using F150 particle size alumina at a processing pressure of 0.4 MPa and a gun / cold-rolled steel plate distance of 3 cm. The surface of the sandblasted area was washed with acetone and then left to stand for 30 minutes at 23°C. Two test pieces were prepared. Next, the first agent of the adhesive composition was applied to the sandblasted area of one of the test pieces to a thickness of 20 μm to prepare test piece 1, and the second agent was applied to the sandblasted area of the other test piece to a thickness of 20 μm to prepare test piece 2. Next, one minute after application of the first agent, the test piece 1 and the test piece 2 are bonded together so that the bonded area is 25 mm × 12.5 mm, the bonded joint is clamped with two modern pinches, and the test piece 1 is fixed in a vice. Next, 20 seconds after bonding, the modern pinches are removed, and 30 seconds after bonding, the test piece 2 is pulled at a tensile speed of 20 mm / min using a mechanical force gauge, and the value of the mechanical force gauge is read, and this value is the tensile shear strength T(1) (MPa). [2] Using a B-type viscometer, the temperature was 25°C and the shear rate was 0.6 s -1The adhesive composition according to [1], wherein the viscosity of the first part and the viscosity of the second part are each 30 mPa·s or more and 2000 mPa·s or less, as measured by the method described above. [3] Using a B-type viscometer, the temperature was 25°C and the shear rate was 5.9 s -1 The adhesive composition according to [1] or [2], wherein the viscosity of the first part and the second part, measured by the method described above, is 20 mPa·s or more and 2000 mPa·s or less. [4] The adhesive composition according to any one of [1] to [3], which has a tensile shear strength T(60) of 0.01 MPa or more as measured according to the following <Tensile shear strength after standing for 60 minutes>. <Tensile shear strength after 60 minutes of standing> A 20 mm area from the edge of a 25 mm wide, 100 mm long, and 1.6 mm thick cold-rolled steel plate (JIS G 3141:2017, SPCC-SD) was sandblasted using F150 particle size alumina at a processing pressure of 0.4 MPa and a gun / cold-rolled steel plate distance of 3 cm. The surface of the sandblasted area was washed with acetone and then left to stand for 30 minutes at 23°C. Two test pieces were prepared. Next, the first agent of the adhesive composition was applied to the sandblasted area of one of the test pieces to a thickness of 20 μm to prepare test piece 1, and the second agent was applied to the sandblasted area of the other test piece to a thickness of 20 μm to prepare test piece 2. Next, 60 minutes after application of the first agent, the test piece 1 and the test piece 2 are bonded together so that the bonded area is 25 mm × 12.5 mm, the bonded joint is clamped with two modern pinches, and the test piece 1 is fixed in a vice. Next, 20 seconds after bonding, the modern pinches are removed, and 30 seconds after bonding, the test piece 2 is pulled at a tensile speed of 20 mm / min using a mechanical force gauge, and the value of the mechanical force gauge is read, and this value is the tensile shear strength T(60) (MPa). [5] The adhesive composition according to any one of [1] to [4], wherein the tensile shear strength T(60) after standing for 60 minutes, measured according to the <Tensile Shear Strength> below, divided by the tensile shear strength T(1) after standing for 1 minute (T(60) / T(1)) is 0.5 or more and 1.5 or less. <Tensile shear strength> A 20 mm area from the edge of a 25 mm wide, 100 mm long, and 1.6 mm thick cold-rolled steel plate (JIS G 3141:2017, SPCC-SD) was sandblasted using F150 particle size alumina at a processing pressure of 0.4 MPa and a gun / cold-rolled steel plate distance of 3 cm. The surface of the sandblasted area was washed with acetone and then left to stand for 30 minutes at 23°C. Four test pieces were prepared. Next, the first agent of the adhesive composition was applied to the sandblasted areas of two of the test pieces to a thickness of 20 μm to form test piece 1, and the second agent was applied to the sandblasted areas of the remaining two test pieces to a thickness of 20 μm to form test piece 2. Next, one of the test pieces 1 and one of the test pieces 2 were bonded together one minute after application of the first agent so that the bonded area was 25 mm x 12.5 mm, the bonded joint was clamped with two modern clamps, and the test piece 1 was fixed in a vice. Next, 20 seconds after bonding, the modern clamps were removed, and 30 seconds after bonding, the test piece 2 was pulled at a tensile speed of 20 mm / min using a mechanical force gauge, and the value read on the mechanical force gauge was taken as the tensile shear strength T(1) (MPa). Also, 60 minutes after application of the first agent, the other of the test pieces 1 and the other of the test pieces 2 were bonded together so that the bonded area was 25 mm x 12.5 mm, the bonded joint was clamped with two modern clamps, and the test piece 1 was fixed in a vice. Next, 20 seconds after lamination, the modern pinch is removed, and 30 seconds after lamination, the test piece 2 is pulled at a tensile speed of 20 mm / min using a mechanical force gauge, and the value of the mechanical force gauge is read, and this value is the tensile shear strength T(60) (MPa). [6] The adhesive composition according to any one of [1] to [5], wherein the radical polymerizable monomer (A) includes a urethane (meth)acrylate and a polyfunctional (meth)acrylate. [7] The adhesive composition according to any one of [1] to [6], wherein the radical polymerizable monomer (A) contains a highly polar monomer. [8] The adhesive composition according to any one of [1] to [7], further comprising an elastomer (D). [9] The adhesive composition according to any one of [1] to [8], wherein the adhesive composition contains a component having a structural unit derived from butadiene.
[10] The adhesive composition according to any one of [1] to [9], wherein the content of the radical polymerizable monomer (A) is 70% by mass or more and 99% by mass or less based on the total amount of the adhesive composition.
[11] The adhesive composition according to any one of [1] to
[10] , wherein the content of the polymerization initiator (B) is 0.1 parts by mass or more and 20 parts by mass or less, when the content of the radical polymerizable monomer (A) is taken as 100 parts by mass.
[12] The adhesive composition according to any one of [1] to
[11] , wherein the content of the reducing agent (C) is 0.01 parts by mass or more and 10 parts by mass or less, when the content of the radical polymerizable monomer (A) is taken as 100 parts by mass.
[13] The adhesive composition according to any one of [1] to
[12] , which is capable of bonding inorganic members together.
[14] An adhesive structure in which two or more inorganic members are adhered, An adhesive structure comprising a cured product of the adhesive composition according to any one of [1] to
[13] between the inorganic members.
[15] A method for manufacturing a bonded structure, comprising: an adhesion step of bonding inorganic members together using an adhesive composition to obtain an adhesive structure, A method for producing an adhesive structure, wherein the adhesive composition is the adhesive composition according to any one of [1] to
[13] .
[16] The bonding step includes:
[15] A method for manufacturing a bonded structure according to the present invention, comprising a step of bonding a first agent-coated surface of the inorganic member coated with the first agent to a second agent-coated surface of the inorganic member coated with the second agent.
[17] A method for producing a polymerization reaction system comprising: a radical polymerizable monomer (A); a polymerization initiator (B); and a reducing agent (C); A composition having a tensile shear strength T(1) of 0.01 MPa or more, measured according to the <Tensile Shear Strength> below. <Tensile shear strength> A two-part adhesive composition is prepared, which comprises a first part containing a radical polymerizable monomer (A) and a polymerization initiator (B), and a second part containing the radical polymerizable monomer (A) and the reducing agent (C). A 20 mm area from the edge of a 25 mm wide, 100 mm long, and 1.6 mm thick cold-rolled steel plate (JIS G 3141:2017, SPCC-SD) was sandblasted using alumina with a particle size of F150 at a processing pressure of 0.4 MPa and a gun / cold-rolled steel plate distance of 3 cm. The surface of the sandblasted area was washed with acetone and then left to stand for 30 minutes at 23 ° C. Two test pieces were prepared. Next, the first agent of the composition was applied to the sandblasted area of one of the test pieces to a thickness of 20 μm to prepare test piece 1, and the second agent was applied to the sandblasted area of the other test piece to a thickness of 20 μm to prepare test piece 2. Next, one minute after application of the first agent, the test piece 1 and the test piece 2 are bonded together so that the bonded area is 25 mm × 12.5 mm, the bonded joint is clamped with two modern pinches, and the test piece 1 is fixed in a vice. Next, 20 seconds after bonding, the modern pinches are removed, and 30 seconds after bonding, the test piece 2 is pulled at a tensile speed of 20 mm / min using a mechanical force gauge, and the value of the mechanical force gauge is read, and this value is the tensile shear strength T(1) (MPa). [Effects of the Invention]
[0011] According to the present invention, it is possible to provide a composition or adhesive composition that can suppress peeling of a bonded structure in which inorganic members are bonded together, even when the bonded structure is processed and transported, as well as a bonded structure and a method for manufacturing a bonded structure that use the composition or adhesive composition. DETAILED DESCRIPTION OF THE INVENTION
[0012] Hereinafter, embodiments of the present invention will be described in detail.
[0013] In this specification, unless otherwise specified, the expression "X to Y" in the description of a numerical range means at least X and at most Y. For example, "1 to 5% by mass" means "at least 1% by mass and at most 5% by mass." In this specification, the content of each component represents the content relative to the total of the first and second agents. In the description of groups (atomic groups) in this specification, when a notation does not specify whether the group is substituted or unsubstituted, it encompasses both groups having no substituents and groups having a substituent. For example, the term "alkyl group" encompasses not only alkyl groups having no substituents (unsubstituted alkyl groups) but also alkyl groups having a substituent (substituted alkyl groups). In this specification, the term "(meth)acrylic" represents a concept that encompasses both acrylic and methacrylic. The same applies to similar terms such as "(meth)acrylate."
[0014] [Adhesive composition] The composition of the present embodiment contains a radical polymerizable monomer (A), a polymerization initiator (B), and a reducing agent (C), and has a tensile shear strength T(1) of 0.01 MPa or more. The composition is preferably an adhesive composition. The adhesive composition of this embodiment is a two-part adhesive composition, which contains a radical polymerizable monomer (A), a polymerization initiator (B), and a reducing agent (C), wherein the first part contains the radical polymerizable monomer (A) and the polymerization initiator (B), and the second part contains the radical polymerizable monomer (A) and the reducing agent (C), and has a tensile shear strength T(1) of 0.01 MPa or more.
[0015] The tensile shear strength of the adhesive composition is measured as follows. A 20 mm area from the edge of a 25 mm wide, 100 mm long, and 1.6 mm thick cold-rolled steel plate (JIS G 3141:2017, SPCC-SD) was sandblasted using F150 particle size alumina at a processing pressure of 0.4 MPa and a gun / cold-rolled steel plate distance of 3 cm. The surface of the sandblasted area was washed with acetone and then left to stand at 23°C for 30 minutes to prepare two test pieces. Next, the first agent of the adhesive composition was applied to the sandblasted area of one test piece to a thickness of 20 μm to prepare test piece 1, and the second agent was applied to the sandblasted area of the other test piece to a thickness of 20 μm to prepare test piece 2. Next, one minute after application of the first agent, test piece 1 and test piece 2 are bonded together so that the bonded area is 25 mm x 12.5 mm, the bonded area is clamped with two modern pinches, and test piece 1 is fixed in a vice. Next, 20 seconds after bonding, the modern pinches are removed, and 30 seconds after bonding, test piece 2 is pulled at a tensile speed of 20 mm / min using a mechanical force gauge, and the value on the mechanical force gauge is read, and this value is the tensile shear strength T(1) (MPa). A modern pinch can be used that has a total length of 54 mm, spring material: 60, spring diameter: 1.2φ, and plate thickness: 0.36 mm. The tensile shear strength T(1) represents a measurement value for the adhesive composition after the first and second parts have been mixed.
[0016] When a two-component adhesive composition is used to bond and temporarily fasten inorganic members together to produce a laminate (bonded structure), peeling can occur in the bonded structure when the resulting bonded structure is subjected to the next processing step or when it is transported or conveyed, causing misalignment of the inorganic members, making it difficult to completely fix the bonded structure with caulking. After extensive investigation, the inventors have found that by setting the tensile shear strength when two inorganic members are bonded together using an adhesive composition to a predetermined lower limit or greater, the adhesive strength between the inorganic members is improved, and peeling of the bonded structure can be suppressed even when the bonded structure in which the inorganic members are bonded together is processed and transported.
[0017] In this embodiment, peeling of the bonded structure refers to peeling of the inorganic members due to insufficient adhesive strength of the adhesive composition between the inorganic members of the bonded structure, as described above. The adhesive composition of the present embodiment can also be used, for example, as an adhesive composition used for temporary bonding before a final step in which inorganic members are completely fixed together.
[0018] In the adhesive composition of this embodiment, the tensile shear strength T(1) is 0.01 MPa or more, preferably 0.02 MPa or more, more preferably 0.03 MPa or more, even more preferably 0.04 MPa or more, even more preferably 0.05 MPa or more, even more preferably 0.10 MPa or more, even more preferably 0.13 MPa or more, even more preferably 0.15 MPa or more, even more preferably 0.18 MPa or more, even more preferably 0.21 MPa or more, even more preferably 0.25 MPa or more, and preferably 2.00 MPa or less, more preferably 1.50 MPa or less. When the tensile shear strength T(1) of the adhesive composition is equal to or greater than the lower limit, peeling of the bonded structure can be suppressed even when the bonded structure in which inorganic members are bonded together is processed and transported. Furthermore, the time required from bonding the inorganic members to proceeding to the transport and conveyance process can be shortened, and the time required from bonding to proceeding to the next process in various processes involving the bonded structure can be shortened. Furthermore, when the tensile shear strength T(1) of the adhesive composition is equal to or less than the upper limit, the resulting cured product of the adhesive composition is given appropriate flexibility, and workability can be further improved when bonding and temporarily fixing inorganic members together and then completely fixing them by caulking or the like.
[0019] The physical properties of the adhesive composition will be further described below.
[0020] In the adhesive composition of this embodiment, when the first agent and the second agent are applied to two inorganic members, respectively, and the two inorganic members are bonded together 60 minutes after application of the first agent, the tensile shear strength T(60) is preferably 0.01 MPa or more, more preferably 0.02 MPa or more, even more preferably 0.03 MPa or more, even more preferably 0.04 MPa or more, even more preferably 0.05 MPa or more, even more preferably 0.10 MPa or more, even more preferably 0.11 MPa or more, even more preferably 0.14 MPa or more, even more preferably 0.15 MPa or more, even more preferably 0.18 MPa or more, even more preferably 0.20 MPa or more, even more preferably 0.22 MPa or more, even more preferably 0.25 MPa or more, and preferably 2.00 MPa or less, more preferably 1.50 MPa or less. When the tensile shear strength T(60) of the adhesive composition is equal to or greater than the above lower limit, peeling of the bonded structure can be suppressed even when the bonded structure in which inorganic members are bonded to each other is processed and transported. Furthermore, when the first and second parts of the adhesive composition are applied to two inorganic members, respectively, and then the two inorganic members are bonded after leaving them for about 60 minutes, the adhesive strength can be further improved in a short time, and peeling of the bonded structure can be further suppressed even when the bonded structure obtained in this way is processed and transported. This makes it possible to carry out a process in which the first and second parts of the adhesive composition are applied in order to a large number of inorganic members, and then the inorganic members are stacked and bonded together in a batch during the manufacturing process of the bonded structure. Furthermore, when the tensile shear strength T(60) of the adhesive composition is equal to or less than the above upper limit, the adhesive composition is given an appropriate degree of flexibility to a cured product thereof, and workability can be further improved when the inorganic member is bonded and temporarily fixed, and then completely fixed by caulking or the like. The tensile shear strength T(60) is measured in the same manner as the tensile shear strength T(1) described above, except that test piece 1 and test piece 2 are bonded together 60 minutes after application of the first agent. The tensile shear strength T(60) represents a measurement value for the adhesive composition after the first and second parts have been mixed.
[0021] The tensile shear strength T(60) after 60 minutes of standing measured according to the above-mentioned measurement method divided by the tensile shear strength T(1) after 1 minute of standing (T(60) / T(1)) is preferably 0.5 or more, more preferably 0.6 or more, even more preferably 0.7 or more, even more preferably 0.8 or more, and preferably 1.5 or less, more preferably 1.4 or less, even more preferably 1.3 or less. When T(60) / T(1) is within the above range, the adhesive strength can be improved in a short time when two inorganic members are bonded together, regardless of the length of time from when the first and second parts of the adhesive composition are applied to the two inorganic members, respectively, until the inorganic members are bonded together, and peeling of the bonded structure can be suppressed even when the bonded structure in which the inorganic members are bonded together is processed and transported. As a result, when the first and second parts of the adhesive composition are applied sequentially to a large number of inorganic members in the process of manufacturing a bonded structure, and the inorganic members are then stacked and bonded together later, the adhesive strength does not change between the inorganic member to which the adhesive composition is applied first and the inorganic member to which the adhesive composition is applied last, making it possible to stably manufacture a bonded structure.
[0022] The adhesive composition of this embodiment was measured using a Brookfield viscometer at a temperature of 25°C and a shear rate of 0.6 s -1 The viscosity of the first and second parts, measured by the viscosities (I / I) method, is preferably 30 mPa·s or more, more preferably 50 mPa·s or more, even more preferably 100 mPa·s or more, even more preferably 150 mPa·s or more, even more preferably 250 mPa·s or more, even more preferably 350 mPa·s or more, and even more preferably 400 mPa·s or more, and is preferably 2000 mPa·s or less, more preferably 1800 mPa·s or less, even more preferably 1700 mPa·s or less, even more preferably 1600 mPa·s or less, even more preferably 1500 mPa·s or less, even more preferably 1300 mPa·s or less, even more preferably 1200 mPa·s or less, even more preferably 1100 mPa·s or less, and even more preferably 1000 mPa·s or less.
[0023] Using a B-type viscometer, the temperature was 25°C and the shear rate was 5.9 s -1 The viscosity of the first and second parts, measured by the viscosities VI, VI, VIH ...
[0024] The above shear rate is 0.6 s -1 and shear rate 5.9 s -1 By ensuring that the viscosity of the first and second agents, as measured by the viscosity test, falls within the above range, the applicability of the first and second agents when applied to an inorganic member is improved, which in turn improves the mixability after bonding two inorganic members together, and the adhesive strength can be improved in a short period of time when the inorganic members are bonded together.
[0025] Next, each component constituting the adhesive composition will be described.
[0026] <Radical polymerizable monomer (A)> The adhesive composition of the present embodiment contains a radical polymerizable monomer (A). The radical polymerizable monomer (A) preferably includes a urethane (meth)acrylate and a polyfunctional (meth)acrylate. This brings the number of crosslinking groups in the radical polymerizable monomer (A) into an appropriate range, and when two inorganic members are bonded together, the adhesive strength can be improved in a short time, and even when the bonded structure in which the inorganic members are bonded together is processed and transported, peeling of the bonded structure can be suppressed.
[0027] A polyfunctional (meth)acrylate refers to a compound having two or more carbon-carbon double bonds such as a (meth)acryloyl group, except for polyfunctional (meth)acrylates that fall under the category of highly polar monomers, which will be described later. The polyfunctional (meth)acrylate of the present embodiment preferably contains three or more (meth)acryloyl groups, more preferably four or more (meth)acryloyl groups, even more preferably five or more (meth)acryloyl groups, even more preferably six or more (meth)acryloyl groups, and preferably contains 10 or less (meth)acryloyl groups, more preferably nine or less (meth)acryloyl groups, even more preferably eight or less (meth)acryloyl groups, and even more preferably seven or less (meth)acryloyl groups. When the number of (meth)acryloyl groups in the polyfunctional (meth)acrylate is equal to or greater than the above lower limit, a larger number of crosslinking groups are formed in the radical polymerizable monomer (A), and when two inorganic members are bonded together, the adhesive strength can be improved in a short time, and even when the bonded structure in which the inorganic members are bonded together is processed and transported, peeling of the bonded structure can be suppressed. Furthermore, when the number of (meth)acryloyl groups in the polyfunctional (meth)acrylate is equal to or less than the above upper limit, the number of crosslinking groups in the radical polymerizable monomer (A) can be kept within an appropriate range, and variations in physical properties due to poor reaction of the (meth)acryloyl groups can be suppressed.
[0028] As the polyfunctional (meth)acrylate, a polyfunctional (meth)acrylate having an aliphatic chain structure can be used. Examples of polyfunctional (meth)acrylates having an aliphatic chain structure include one or more selected from the group consisting of isocyanuric acid ethylene oxide-modified tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane propylene oxide-modified tri(meth)acrylate, trimethylolpropane ethylene oxide-modified tri(meth)acrylate, diglycerin ethylene oxide-modified (meth)acrylate, tris[(meth)acryloyloxyethyl]isocyanurate, ditrimethylolpropane tetra(meth)acrylate, dimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol ethoxy tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. Among the polyfunctional (meth)acrylates, it is preferable to use a polyfunctional acrylate from the viewpoint of further improving the curing rate of the adhesive composition.
[0029] Among these, it is preferable to use a polyfunctional (meth)acrylate having an aliphatic chain structure, more preferably to use one or more selected from the group consisting of dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and trimethylolpropane tri(meth)acrylate, even more preferably to use one or two selected from the group consisting of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate, and even more preferably to use dipentaerythritol hexaacrylate. Commercially available polyfunctional (meth)acrylates include DPHA M402 manufactured by Toagosei Co., Ltd. and TMPT-M manufactured by Shin-Nakamura Chemical Co., Ltd.
[0030] The content of the polyfunctional (meth)acrylate in the adhesive composition is preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, even more preferably 8 parts by mass or more, even more preferably 15 parts by mass or more, even more preferably 25 parts by mass or more, even more preferably 35 parts by mass or more, even more preferably 45 parts by mass or more, even more preferably 55 parts by mass or more, and is preferably 90 parts by mass or less, more preferably 85 parts by mass or less, preferably 80 parts by mass or less, based on 100 parts by mass of the radical polymerizable monomer (A). When the content of the polyfunctional (meth)acrylate is equal to or greater than the lower limit, a larger number of crosslinking groups are formed in the radically polymerizable monomer (A), and when two inorganic members are bonded together, the adhesive strength can be improved in a short time, and peeling of the bonded structure can be more effectively prevented even when the bonded structure in which the inorganic members are bonded together is processed and transported. Furthermore, when the content of the polyfunctional (meth)acrylate is equal to or less than the upper limit, the adhesive composition can be prevented from curing too quickly, and variations in physical properties due to poor reaction of the (meth)acryloyl groups can be more effectively suppressed, and coatability can be more effectively improved.
[0031] Urethane (meth)acrylate is a compound having a urethane bond and a (meth)acryloyl group. When the radical polymerizable monomer (A) contains a urethane (meth)acrylate, the viscosity of the adhesive composition can be adjusted to a more appropriate range, which in turn can further improve the applicability. The urethane (meth)acrylate preferably has two (meth)acryloyl groups, which allows the number of crosslinking groups in the radical polymerizable monomer (A) to be within an appropriate range, thereby improving the adhesive strength in a short time when bonding two inorganic members together and improving the coatability, and ultimately preventing peeling of the bonded structure when the bonded structure in which the inorganic members are bonded together is processed and transported.
[0032] (A) Urethane (meth)acrylate refers to a urethane (meth)acrylate having a urethane bond in the molecule, which is obtained, for example, by reacting (e.g., polycondensation reaction) a polyol compound (hereinafter represented by X), an organic polyisocyanate compound (hereinafter represented by Y), and a hydroxy (meth)acrylate (hereinafter represented by Z). Examples of the polyol compound (X) (hereinafter, sometimes simply referred to as polyol) include polyether types and polyester types. The polyol may be a polyhydric alcohol. Among the polyols, one or more types selected from polybutadiene having hydroxyl groups at both ends, neopentyl glycol, tetramethylene glycol, butanediol, hexanediol, and polyester polyols are preferred, and one or two types selected from polybutadiene having hydroxyl groups at both ends and tetramethylene glycol are more preferred. Examples of polybutadiene having hydroxyl groups at both ends include polyols having a 1,2-polybutadiene structure. The organic polyisocyanate compound (Y) (hereinafter sometimes simply referred to as isocyanate) may be, for example, an aromatic, aliphatic, alicyclic, alicyclic, etc. Among the isocyanates, one or more selected from toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HMDI), and hydrogenated diphenylmethane diisocyanate (hydrogenated MDI) are preferred, and one or two selected from toluene diisocyanate and isophorone diisocyanate are more preferred. The hydroxy(meth)acrylate (Z) (hereinafter sometimes simply referred to as hydroxy(meth)acrylate) is preferably a hydroxyalkyl(meth)acrylate. Among the hydroxyalkyl (meth)acrylates, the hydroxyalkyl (meth)acrylate represented by formula (1) is preferred. Formula (1) ZO-(R 1 -O-)pH (wherein Z is a (meth)acryloyl group, R 1represents an alkylene group, and p represents an integer of 1 to 10. R in Equation (1) 1 The alkylene group preferably has 1 to 8 carbon atoms, more preferably 2 to 6 carbon atoms. Among the hydroxyalkyl (meth)acrylates, one or more selected from 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate are preferred, with 2-hydroxyethyl (meth)acrylate being more preferred. Urethane (meth)acrylates can be produced, for example, according to the descriptions in JP-A Nos. 7-25957, 2002-173515, 7-292048, and 2000-351819.
[0033] As the urethane (meth)acrylate, commercially available products can be used, including the following: U-200PA, UA-W2, UA-W2A, UA-122P, UA-160TM, UA-2235PE, UA-4200, UA-4400, UA-7000, UA-31F, UA-7100, U-2HA, U-2PPA, U-6LPA, U-10PA, U-10HA, UA-33H, UA-53H, UA-32P, UA-1100H, and the like, manufactured by Shin-Nakamura Chemical Co., Ltd. Negami Kogyo's UN-350, UN-352, UN353, UN-1255, UN-2600, UN-2700, UN-5500, UN-5590, UN-5507, UN-6060PTM, UN-6060S, UN6200, UN-6202, UN-6303, U N-6304, UN-6305, UN-7600, UN-7700, UN-9000PEP, UN-9200A, UN-3320HA, UN-3320HC, UN-3320HS, UN-904, UN-906S, UN-901T, UN-905, UN-952, etc. Kyoeisha's AH-600, UA-306H, UA-306T, UA-306I, UA-510H, UF-8001G, DAUA-167, BPZA-66, etc. Miramer PU210, Miramer PU256, Miramer PU2050, Miramer PU2100, Miramer PU2300C, Miramer PU2560, Miramer PU320, Miramer PU340, Miramer PU3000, Miramer PU3200, Miramer PU3450, Miramer PU5000, Miramer PU610, Miramer PU6510, Miramer PU9500, Miramer PU9800, Miramer UA5216, Miramer SC2100, Miramer SC2152, Miramer SC2404, Miramer SC2565, Miramer MU3603, Miramer PU370, Miramer PU640, Miramer PU2421NT, etc. manufactured by MIWON EBECRYL 210, EBECRYL 220, EBECRYL 4500, EBECRYL 230, EBECRYL 270, EBECRYL 280 / 15IB, EBECRYL 284, EBECRYL 4491, EBECRYL 4683, EBECRYL 4858, EBECRYL 8307, EBECRYL 8402, EBECRYL 8411, EBECRYL 8413, EBECRYL 8804, EBECRYL 8807, EBECRYL 9270, EBECRYL 7735, KRM8961, EBECRYL 8800, EBECRYL 1259, 294 / 25HD, EBECRYL 4100, EBECRYL 4220, EBECRYL 4513, EBECRYL 4740, EBECRYL 4820, EBECRYL 8311, EBECRYL 8465, EBECRYL 9260, EBECRYL 8701, EBECRYL 8667, EBECRYL 8701, KRM 8667, KRM 8296, EBECRYL 4587, EBECRYL 4200, EBECRYL 4666, EBECRYL 4680, EBECRYL 8210, EBECRYL 8405, KRT 8528, EBECRYL 1290, EBECRYL 5129, EBECRYL 8254, EBECRYL 8301R, KRM 8200, KRM 8200AE, KRM 8530, KRM 8904, KRM 8531BA, KRM 8452, etc. manufactured by Daicel Ornex Co., Ltd. Sartomer (registered trademark) CN910, CN959, CN963, CN964, CN965, CN966, CN969 NS, CN980 NS, CN981 NS, CN982, CN983 NS, CN985, CN991 NS, CN996 NS, CN2920, CN8881 NS, CN8883 NS, CN9001 NS, CN9004, CN9005, CN9009, CN9011, CN9021 NS, CN9023, CN9028, CN9030, CN9178 NS, CN9290, CN9893 NS, CN929, CN989 NS, CN968 NS, CN9006 NS, CN9010, manufactured by Arkema Inc. NS, CN9025, CN9026, CN9039, CN9062, CN9110 NS, CN9029, CN8885 NS, CN9013 NS, CN973, CN978 NS, CN992, CN9167, CN9782, CN9783, CN970, CN971, CN972, CN975 NS, CN9165 etc. Furthermore, when the radical polymerizable monomer (A) contains a component having a structural unit derived from butadiene, which will be described later, an example of a urethane (meth)acrylate having a structural unit derived from butadiene is TE2000 manufactured by Nippon Soda Co., Ltd.
[0034] The number average molecular weight of the urethane (meth)acrylate is preferably 1,000 or more, more preferably 1,500 or more, even more preferably 2,000 or more, and preferably 10,000 or less, more preferably 8,000 or less, even more preferably 5,000 or less. When the number average molecular weight of the urethane (meth)acrylate is within the above range, the number of moles of the polyol portion falls within an appropriate range, which further improves the flexibility of the adhesive composition and, in turn, further improves the coatability. The number average molecular weight of the urethane (meth)acrylate can be measured by gel permeation chromatography (GPC). For example, the following measurement conditions can be used for GPC. The number average molecular weight Mn of urethane (meth)acrylate is measured using GPC (Tosoh Corporation's "HLC-8120GPC"), with tetrahydrofuran (THF) as the solvent, polystyrene as the standard sample, and TSKgel super H1000+H2000+H3000 as the columns, at a flow rate of 0.5 mL / min and a column oven temperature of 40°C.
[0035] The acrylic equivalent of the urethane (meth)acrylate is preferably 1000 or more, more preferably 1200 or more, even more preferably 1500 or more, and preferably 3000 or less, more preferably 2800 or less, even more preferably 2600 or less, even more preferably 2500 or less, even more preferably 2300 or less. When the acrylic equivalent of the urethane (meth)acrylate is within the above range, crosslinking groups in the radical polymerizable monomer (A) can be formed appropriately, and the flexibility of the resulting adhesive can be further improved. The acrylic equivalent of the urethane (meth)acrylate is given by the following formula (2). Acrylic equivalent: e = A / B (2) where: A: Weight average molecular weight measured by size exclusion chromatography in terms of polystyrene B: Number of (meth)acrylate groups in one urethane (meth)acrylate molecule Shows.
[0036] The viscosity of the urethane (meth)acrylate is preferably 50 Pa·s or more, more preferably 75 Pa·s or more, even more preferably 100 Pa·s or more, preferably 125 Pa·s or more, and preferably 1000 Pa·s or less, more preferably 750 Pa·s or less, even more preferably 500 Pa·s or less, even more preferably 300 Pa·s or less. When the viscosity of the urethane (meth)acrylate is within the above range, the viscosity of the resulting adhesive composition can be set within an appropriate range, which in turn can improve the coatability. The viscosity of the urethane (meth)acrylate is measured at 45°C using a Brookfield viscometer.
[0037] The content of the urethane (meth)acrylate in the adhesive composition is preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and even more preferably 8 parts by mass or more, and is preferably 80 parts by mass or less, more preferably 75 parts by mass or less, even more preferably 70 parts by mass or less, even more preferably 65 parts by mass or less, even more preferably 60 parts by mass or less, even more preferably 55 parts by mass or less, even more preferably 40 parts by mass or less, even more preferably 30 parts by mass or less, even more preferably 25 parts by mass or less, and even more preferably 15 parts by mass or less, based on 100 parts by mass of the radical polymerizable monomer (A). When the content of the urethane (meth)acrylate is equal to or greater than the above lower limit, the adhesive composition can be more easily applied. When the content of the urethane (meth)acrylate is equal to or less than the above upper limit, the adhesive strength can be improved in a short time when two inorganic members are bonded together, and peeling of the bonded structure can be more effectively prevented when the bonded structure in which the inorganic members are bonded together is processed and transported. When the adhesive composition contains the elastomer (D) described below, it may contain the elastomer (D) without containing the urethane (meth)acrylate, which allows the cured product of the adhesive composition to have more appropriate flexibility.
[0038] The total content of the urethane (meth)acrylate and the polyfunctional (meth)acrylate in the adhesive composition is preferably 40 parts by mass or more, more preferably 50 parts by mass or more, preferably 60 parts by mass or more, preferably 70 parts by mass or more, and preferably 90 parts by mass or less, more preferably 85 parts by mass or less, and even more preferably 80 parts by mass or less, when the content of the radically polymerizable monomer (A) is taken as 100 parts by mass. When the total content of the urethane (meth)acrylate and the polyfunctional (meth)acrylate is within the above ranges, the coatability of the adhesive composition is further improved, and when two inorganic members are bonded together, the adhesive strength can be further improved in a short period of time, and peeling of the bonded structure can be further suppressed even when the bonded structure in which the inorganic members are bonded together is processed and transported.
[0039] The radical polymerizable monomer (A) may further contain a highly polar monomer. The highly polar monomer is a polymerizable monomer having a polar functional group and a carbon-carbon double bond. The highly polar monomer may be a monofunctional monomer (a monomer having one carbon-carbon double bond) or a polyfunctional monomer (a monomer having multiple carbon-carbon double bonds), but is preferably a monofunctional monomer.
[0040] From the viewpoint of further improving the interaction with inorganic components, the polar functional group possessed by the highly polar monomer preferably contains one or more types selected from the group consisting of a carboxy group, a hydroxy group, and a phosphate group, more preferably contains one or more types selected from the group consisting of a carboxy group and a phosphate group, and even more preferably contains a carboxy group.
[0041] The highly polar monomer preferably contains one or more selected from the group consisting of (meth)acrylic acid, fumaric acid, maleic acid, fumaric anhydride, maleic anhydride, a monomer having a phosphate group and a (meth)acryloyl group, and a hydroxyalkyl (meth)acrylate, more preferably contains one or more selected from the group consisting of (meth)acrylic acid and a monomer having a phosphate group and a (meth)acryloyl group, even more preferably contains (meth)acrylic acid, and even more preferably contains methacrylic acid, which can further improve the interaction with the inorganic member.
[0042] The content of the highly polar monomer in the adhesive composition is preferably 1 part by mass or more, preferably 5 parts by mass or more, preferably 10 parts by mass or more, preferably 15 parts by mass or more, preferably 20 parts by mass or more, and preferably 50 parts by mass or less, more preferably 45 parts by mass or less, preferably 40 parts by mass or less, preferably 35 parts by mass or less, preferably 30 parts by mass or less, based on 100 parts by mass of the radical polymerizable monomer (A). By ensuring that the content of the highly polar monomer is within the above range, it is possible to further improve the interaction with the inorganic member, and when two inorganic members are bonded together, it is possible to further improve the adhesive strength in a short period of time, and it is possible to further suppress peeling of the bonded structure even when the bonded structure in which the inorganic members are bonded together is processed and transported.
[0043] The content of the radical polymerizable monomer (A) in the adhesive composition is preferably 70% by mass or more, more preferably 75% by mass or more, even more preferably 80% by mass or more, even more preferably 85% by mass or more, even more preferably 90% by mass or more, and even more preferably 93% by mass or more, based on the total adhesive composition, and may be, for example, 99% by mass or less, or 98% by mass or less. When the content of the radical polymerizable monomer (A) is within the above range, the adhesive strength can be improved in a short time when two inorganic members are bonded together, and even when the bonded structure in which the inorganic members are bonded together is processed and transported, peeling of the bonded structure can be more effectively suppressed, and the physical properties of the resulting bonded structure can be more improved.
[0044] <Components containing structural units derived from butadiene> The adhesive composition of the present embodiment preferably contains a component having a structural unit derived from butadiene. The first and second parts of the adhesive resin composition are applied to two inorganic members, respectively, and the two members are then bonded together. The first and second parts are mixed, generating radicals, initiating a propagation reaction. During this process, oxygen contained in the adhesive generates peroxy radicals, which have low propagation activity, significantly slowing the curing rate. However, when the radical-polymerizable monomer (A) contains a component with a butadiene-derived structural unit, the peroxy radicals abstract the allylic hydrogen atoms of the butadiene, generating carbon radicals with high propagation activity. This suppresses the decrease in curing rate, and ultimately improves the adhesive strength in a short time when bonding two inorganic members.
[0045] The content of the component having a structural unit derived from butadiene in the adhesive composition is preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and even more preferably 8 parts by mass or more, and is preferably 80 parts by mass or less, even more preferably 60 parts by mass or less, even more preferably 50 parts by mass or less, even more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less, when the total amount of the adhesive composition is 100 parts by mass. When the content of the component having a butadiene-derived structural unit is within the above range, the influence of oxygen is reduced during the period from when the first and second parts of the adhesive composition are applied to two inorganic members, respectively, until the two inorganic members are bonded together, and thus a decrease in the curing rate when the inorganic members are bonded together can be suppressed. Furthermore, when the two inorganic members are bonded together, the adhesive strength can be further improved in a short period of time, and even when the bonded structure in which the inorganic members are bonded together is processed and transported, peeling of the bonded structure can be further suppressed.
[0046] The component having a butadiene-derived structural unit may be contained in any of the components in the adhesive composition, and is preferably contained in one or more selected from the group consisting of urethane (meth)acrylate, polyfunctional (meth)acrylate, and highly polar monomer in the radical polymerizable monomer (A), and the elastomer (D) described below. From the viewpoint of further improving the flexibility of the cured product of the adhesive resin composition obtained, it is more preferable that it be contained in one or two selected from the group consisting of urethane (meth)acrylate and elastomer (D). It is even more preferable that it be contained in urethane (meth)acrylate, from the viewpoint of further improving the adhesive strength in a short time when two inorganic members are bonded together and further suppressing peeling of the bonded structure even when the bonded structure in which the inorganic members are bonded together is processed and transported.
[0047] When the radical polymerizable monomer (A) contains a component having a structural unit derived from butadiene, the number of structural units derived from butadiene in the component having a structural unit derived from butadiene is preferably 10 or more, more preferably 15 or more, even more preferably 20 or more, even more preferably 25 or more, even more preferably 30 or more, and preferably 70 or less, more preferably 60 or less, even more preferably 55 or less, even more preferably 50 or less. By having the number of butadiene-derived structural units equal to or greater than the above lower limit, when two inorganic members are bonded together, the adhesive strength can be improved in a short time, the flexibility of the cured product can be improved, and peeling of the bonded structure can be more effectively prevented even when the bonded structure in which the inorganic members are bonded together is processed and transported. Furthermore, by having the number of butadiene-derived structural units equal to or less than the above upper limit, the flexibility of the cured product of the adhesive composition can be kept within a more appropriate range. The butadiene-derived structural unit may be contained at the terminal of each component in the radical polymerizable monomer (A) or may be contained in the main chain.
[0048] <Elastomer (D)> The adhesive composition of the present embodiment may further contain an elastomer (D). The elastomer (D) preferably contains one or more selected from the group consisting of butadiene rubber, (meth)acrylonitrile-butadiene rubber, and styrene-butadiene rubber, and more preferably (meth)acrylonitrile-butadiene rubber. This allows the elastomer (D) to contain a component having a structural unit derived from butadiene, which further suppresses a decrease in the curing rate, further improves the adhesive strength in a short period of time when bonding two inorganic members, and suppresses peeling of the bonded structure even when the bonded structure in which the inorganic members are bonded is processed and transported, while further improving the flexibility of the cured product of the adhesive composition. In the elastomer (D), the portion having a structural unit derived from butadiene is also called a soft segment unit and exhibits rubber elasticity.
[0049] The content of butadiene-derived structural units in the elastomer (D) is preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, even more preferably 60% by mass or more, even more preferably 70% by mass or more, and preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less. When the content of the butadiene-derived structural unit in the elastomer (D) is equal to or greater than the above lower limit, the adhesive strength can be improved in a short time when two inorganic members are bonded together, and when the bonded structure in which the inorganic members are bonded together is processed and transported, peeling of the bonded structure can be more effectively prevented, and the flexibility of the cured product of the adhesive composition can be more effectively improved. Furthermore, when the content of the butadiene-derived structural unit in the elastomer (D) is equal to or less than the above upper limit, the flexibility of the cured product of the adhesive composition can be kept within a more appropriate range.
[0050] The content of the elastomer (D) is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and even more preferably 8% by mass or more, based on the total adhesive composition, and is preferably 20% by mass or less, more preferably 18% by mass or less, even more preferably 15% by mass or less, even more preferably 13% by mass or less, and even more preferably 10% by mass or less. By having the content of the elastomer (D) within the above range, when two inorganic members are bonded together, the adhesive strength can be improved in a short time, the flexibility of the cured product of the adhesive composition can be improved, and peeling of the bonded structure can be more effectively suppressed even when the bonded structure in which the inorganic members are bonded together is processed and transported.
[0051] Furthermore, the content of the elastomer (D) is preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and even more preferably 8 parts by mass or more, and is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less, when the total content of the radical polymerizable monomer (A) and the elastomer (D) is 100 parts by mass. By ensuring that the content of the elastomer (D) is within the above range, when two inorganic members are bonded together, the adhesive strength can be improved in a short time, the flexibility of the cured product of the adhesive composition can be improved, and peeling of the bonded structure can be more effectively prevented even when the bonded structure in which the inorganic members are bonded together is processed and transported.
[0052] <Polymerization initiator (B)> The adhesive composition of the present embodiment contains a polymerization initiator (B). The polymerization initiator (B) polymerizes the carbon-carbon double bond of the radically polymerizable monomer (A), and when two inorganic members are bonded together, the adhesive strength can be further improved in a short time, and further, peeling of the bonded structure can be further suppressed even when the bonded structure in which the inorganic members are bonded together is processed and transported.
[0053] The polymerization initiator (B) preferably contains a thermal radical polymerization initiator. From the viewpoint of further improving reactivity, the thermal radical polymerization initiator preferably contains an organic peroxide, more preferably contains one or more selected from the group consisting of cumene hydroperoxide, paramenthane hydroperoxide, tertiary butyl hydroperoxide, diisopropylbenzene dihydroperoxide, methyl ethyl ketone peroxide, and tertiary butyl peroxybenzoate, and even more preferably contains cumene hydroperoxide.
[0054] The content of the polymerization initiator (B) in the adhesive composition of the present embodiment is, relative to 100 parts by mass of the content of the radical polymerizable monomer (A), preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 1.0 parts by mass or more, even more preferably 1.5 parts by mass or more, and even more preferably 2.0 parts by mass or more, and is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, even more preferably 10 parts by mass or less, even more preferably 8 parts by mass or less, even more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less. When the content of the polymerization initiator (B) is within the above range, the crosslinking reaction after bonding two inorganic members proceeds appropriately, and when the two inorganic members are bonded, the adhesive strength can be further improved in a short time. In turn, even when the bonded structure in which the inorganic members are bonded to each other is processed and transported, peeling of the bonded structure can be further suppressed.
[0055] <Reducing Agent (C)> The adhesive composition of the present embodiment contains a reducing agent (C). The adhesive composition of the present embodiment can further improve its curability by using a polymerization initiator (B) and a reducing agent (C) in combination. The reducing agent (C) may be any reducing agent that reacts with the polymerization initiator (B) to generate radicals. The reducing agent (C) preferably includes one or more selected from the group consisting of tertiary amines, thiourea derivatives, and transition metal salts, and more preferably includes one or two selected from the group consisting of tertiary amines and transition metal salts.
[0056] Examples of the tertiary amine include one or more selected from the group consisting of triethylamine, tripropylamine, tributylamine, and N,N-dimethyl-p-toluidine. Examples of the thiourea derivative include one or more selected from the group consisting of 2-mercaptobenzimidazole, methylthiourea, dibutylthiourea, ethylenethiourea, acetyl-2-thiourea, benzoylthiourea, N,N-diphenylthiourea, N,N-diethylthiourea, N,N-dibutylthiourea, and tetramethylthiourea. Examples of the transition metal salt include one or more selected from the group consisting of cobalt naphthenate, copper naphthenate, vanadyl acetylacetonate, etc. The transition metal salt more preferably includes vanadyl acetylacetonate.
[0057] The content of the reducing agent (C) in the adhesive composition of this embodiment is, when the content of the radical polymerizable monomer (A) is taken as 100 parts by mass, preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, even more preferably 0.25 parts by mass or more, even more preferably 0.5 parts by mass or more, even more preferably 0.6 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, even more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, even more preferably 1 part by mass or less. When the content of the reducing agent (C) is within the above range, the crosslinking reaction after bonding two inorganic members proceeds appropriately, and when the two inorganic members are bonded, the adhesive strength can be further improved in a short time, and even when the bonded structure in which the inorganic members are bonded to each other is processed and transported, peeling of the bonded structure can be further suppressed.
[0058] <Two-dose formulation> The adhesive composition of this embodiment is a two-component composition. A two-dose formulation is one in which two drugs are filled in separate containers and mixed immediately before use. In the adhesive composition of the present embodiment, the polymerization initiator (B) is preferably contained in the first part, and the reducing agent (C) is preferably contained in the second part. It is preferable to adjust the amount of each component in the first and second parts so that the adhesive composition after mixing the first and second parts contains each component within the above-mentioned preferred content range.
[0059] <Method for producing adhesive composition> In producing the adhesive composition of the present embodiment, it is preferable to appropriately adjust the mixing order, mixing method, etc. of the components. In producing the adhesive composition of this embodiment, it is preferable to first thoroughly mix the radical polymerizable monomer (A) and elastomer (D). As shown in the examples below, it is preferable to thoroughly and uniformly mix the radical polymerizable monomer (A) and elastomer (D) at 50 to 80°C to form a mixture, and then add other components to the mixture and stir. This is believed to ensure that the radical polymerizable monomer (A) and elastomer (D) are thoroughly and uniformly mixed. Adhesive compositions produced in this manner tend to more easily satisfy the properties, such as the tensile shear adhesive strength, described above, compared to adhesive compositions obtained by other production methods.
[0060] The adhesive composition of the present embodiment can bond inorganic members such as metals and magnets to each other. More specifically, the adhesive composition of the present embodiment can be suitably used as an automotive adhesive used in the manufacture of automobiles, and can be more suitably used as an adhesive for motors, and can be even more suitably used as an adhesive for fixing between a magnet and a rotor, between a magnet and a stator, and between the steel plates that form the rotor in a motor. The adhesive composition of this embodiment can also be suitably used as an adhesive for fixing a magnet to a metal in a field magnet portion of a speaker.
[0061] [Adhesive structure] The bonded structure of this embodiment is a bonded structure in which two or more inorganic members are bonded together, and contains a cured product of the adhesive composition of this embodiment between the inorganic members. In the bonded structure of the present embodiment, two or more inorganic members are bonded together using the adhesive composition of the present embodiment, and therefore peeling of the bonded structure can be suppressed even when the bonded structure in which the inorganic members are bonded together is processed and transported.
[0062] [Method of manufacturing bonded structure] The method for producing a bonded structure of this embodiment includes a bonding step of bonding inorganic members together using the adhesive composition of this embodiment described above to obtain a bonded structure. The bonding process may further include a process of applying a first agent to an inorganic member, a process of applying a second agent to an inorganic member, and a process of bonding the first agent-coated surface of the inorganic member to which the first agent has been applied and the second agent-coated surface of the inorganic member to which the second agent has been applied. The first and second parts can be applied to the inorganic member using an inkjet or the like. The process of applying the first and second agents to the inorganic member and the process of bonding the first agent-coated surface of the inorganic member coated with the first agent and the second agent-coated surface of the inorganic member coated with the second agent can be carried out at room temperature (23°C). By keeping the temperature at 15°C or higher, the adhesive strength improves when bonding inorganic members in a short time. Furthermore, by keeping the temperature at 30°C or lower, curing does not occur too quickly when bonding inorganic members in a short time, improving workability. The method for producing a bonded structure of this embodiment uses the adhesive composition of this embodiment, and therefore can suppress peeling of the bonded structure even when the bonded structure in which inorganic members are bonded to each other is processed and transported. Therefore, the obtained bonded structure can be stably advanced to a transport or conveyance step, and can also be stably advanced to the next step in various steps that handle the bonded structure. Furthermore, when the adhesive composition of this embodiment contains a component having a structural unit derived from butadiene, even if a time is allowed between the step of applying a first agent to an inorganic member and the step of applying a second agent to an inorganic member and the step of bonding the first-agent-coated surface of the inorganic member coated with the first agent and the second-agent-coated surface of the inorganic member coated with the second agent, bonding can be achieved in a short time after bonding, and adhesive strength can also be improved. The time between the step of applying a first agent to an inorganic member and the step of applying a second agent to an inorganic member and the step of bonding the first-agent-coated surface of the inorganic member coated with the first agent and the second-agent-coated surface of the inorganic member coated with the second agent can be, specifically, 60 minutes or less. Within this time, adhesive strength can be improved in a short time when inorganic members coated with the first agent or the second agent are bonded, and peeling of the bonded structure can be suppressed even when the bonded structure in which the inorganic members are bonded is processed and transported.
[0063] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various other configurations can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of achieving the object of the present invention are included in the present invention. [Example]
[0064] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0065] The following materials were used for the adhesive composition. <Radical polymerizable monomer (A)> Urethane (meth)acrylate 1: Aliphatic polyether urethane acrylate, acryloyl groups per molecule: 2, number average molecular weight: 12,000, polyol: tetramethylene glycol, isocyanate: isophorone diisocyanate, hydroxy (meth)acrylate: 2-hydroxyethyl acrylate Urethane (meth)acrylate 2: 1,2-polybutadiene type methacrylate, TE2000, viscosity: 150 Pa·s, acrylic equivalent: 2000, methacryloyl groups per molecule: 2, number average molecular weight: 2,500, polyol: polyol with 1,2-polybutadiene structure, isocyanate: toluene diisocyanate, hydroxy (meth)acrylate: 2-hydroxyethyl methacrylate, manufactured by Nippon Soda Co., Ltd. Highly polar monomer 1: methacrylic acid, AM, manufactured by Mitsubishi Gas Chemical Co., Ltd. Multifunctional (meth)acrylate 1: Dipentaerythritol penta- and hexaacrylate, DPHA M402, manufactured by Toagosei Co., Ltd. Multifunctional (meth)acrylate 2: Trimethylolpropane trimethacrylate, TMPT-M, manufactured by Shin-Nakamura Chemical Co., Ltd. Monofunctional (meth)acrylate 1: Isobornyl methacrylate, IB-X Monofunctional (meth)acrylate 2: Methyl methacrylate, MMA, manufactured by Mitsubishi Chemical Corporation Monofunctional (meth)acrylate 3: 2-hydroxyethyl methacrylate, 2HEMA, manufactured by Nippon Shokubai Co., Ltd. Monofunctional (meth)acrylate 4: dimethylacrylamide, DMAA, manufactured by KJ Chemicals Co., Ltd. Monofunctional (meth)acrylate 5: Diethylacrylamide, DEAA, manufactured by KJ Chemicals Co., Ltd. Monofunctional (meth)acrylate 6: acryloylmorpholine, ACMO, manufactured by KJ Chemicals Co., Ltd. N-vinyl-2-pyrrolidone, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.
[0066] <Elastomer (D)> Elastomer 1: Acrylonitrile-butadiene rubber, manufactured by JSR Corporation, N250SL (acrylonitrile content: 19.5% by mass, butadiene-derived structural unit content: 81% by mass) <Polymerization initiator (B)> Polymerization initiator 1: Cumene hydroperoxide, PH-80, manufactured by NOF Corporation <Reducing Agent (C)> Reducing agent 1: Vanadyl acetylacetonate, VOAA2, manufactured by Shinko Chemical Industry Co., Ltd. Reducing agent 2: Triethylamine, manufactured by Tokyo Chemical Industry Co., Ltd.
[0067] <Examples 1 to 11 and Comparative Examples 1 to 7> The components were thoroughly mixed in the proportions (unit: parts by mass) shown in Tables 1 to 3 using a stirring device equipped with stirring blades to prepare the first and second parts, respectively. In preparing the first and second parts, the components of the radical polymerizable monomer (A) were mixed thoroughly and uniformly at 50 to 80° C. The other components were then added to the mixture and stirred, followed by degassing to prepare the first and second parts, respectively. Example 12 The components were thoroughly mixed in the proportions (unit: parts by mass) shown in Table 3 using a stirring device equipped with stirring blades to prepare the first and second parts, respectively. In preparing the first and second parts, first, elastomer 1 was added to highly polar monomer 1 and thoroughly mixed at 50 to 80°C using a stirring device equipped with a stirring blade, then polyfunctional (meth)acrylate 2 was added and further mixed to form a mixture. Next, other components were added to the mixture and stirred, and then the mixture was degassed to prepare the first and second parts, respectively. The following evaluations were carried out using the first and second agents obtained in Examples 1 to 12 and Comparative Examples 1 to 7. The results are shown in Tables 1 to 3.
[0068] <Viscosity of urethane (meth)acrylate> The viscosity of urethane (meth)acrylate 2 was measured at 45°C using a Brookfield viscometer.
[0069] <Viscosity of adhesive composition> The first and second parts of the adhesive composition of each example were measured using a Brookfield type viscometer (product name: RVDV2T, manufacturer: Brookfield) at a temperature of 25°C and a shear rate of 0.6 s -1Similarly, the viscosity of each of the first and second adhesive compositions of each example was measured at a temperature of 25°C and a shear rate of 5.9 s -1 The viscosity was measured.
[0070] <Tensile shear strength> Using the first and second parts of the adhesive composition of each example, the tensile shear strength T(1) and the tensile shear strength T(60) were measured as follows. A 20 mm area from the edge of a 25 mm wide, 100 mm long, and 1.6 mm thick cold-rolled steel plate (JIS G 3141:2017, SPCC-SD) was sandblasted using alumina with a particle size of F150 at a processing pressure of 0.4 MPa and a gun / cold-rolled steel plate distance of 3 cm. The surface of the sandblasted area was washed with acetone and then left to stand for 30 minutes at 23 ° C. Two test pieces were prepared. Next, the first agent of the adhesive composition of each example was applied to the sandblasted area of one test piece to a thickness of 20 μm to prepare test piece 1, and the second agent was applied to the sandblasted area of the other test piece to a thickness of 20 μm to prepare test piece 2. Next, test piece 1 and test piece 2 were bonded together one minute after application of the first agent (referred to as 1 minute of open time in Tables 1 to 3) so that the bonded area was 25 mm × 12.5 mm. The bonded area was clamped with two modern pinches (total length 54 mm, spring material: 60, spring diameter: 1.2φ, plate thickness 0.36 mm, manufactured by Nanki Seisakusho Co., Ltd.), and test piece 1 was fixed in a vice. Next, 20 seconds after bonding, the modern pinches were removed, and 30 seconds after bonding, test piece 2 was manually pulled at a tensile speed of 20 mm / min using a mechanical force gauge (product name: FB-500N, manufacturer: Imada). The value of the mechanical force gauge was read, and this value was taken as the tensile shear strength T(1) (MPa). In addition, the tensile shear strength T(60) (MPa) was measured in the same manner as above, except that test pieces 1 and 2 were bonded together 60 minutes after application of the first agent (in Tables 1 to 3, the open time was listed as 60 minutes). The value of T(60) / T(1) was calculated from the obtained values of tensile shear strength T(1) and tensile shear strength T(60).
[0071] <Evaluation of peeling of adhesive structures> Using the first and second parts of the adhesive composition of each example, the bonded structure after bonding the inorganic member was evaluated for the presence or absence of peeling, as follows. Eight inorganic members (material: cold-rolled steel plate, length 100 mm, width 25 mm, thickness 1.6 mm) were prepared. The first agent was applied to one inorganic member, and the second agent was applied to the remaining seven inorganic members using a dropper. One minute after the start of application, the first-agent-applied surface and the second-agent-applied surface of one of the seven inorganic members were bonded together and pressed together for 30 seconds to obtain a bonded structure 1 in which two inorganic members were bonded (Step 1). Next, the first agent was applied to the adhesive-free surface of the inorganic member of the bonded structure 1 to which the second agent had been applied. One minute after the start of application of the first agent to the bonded structure 1, the second-agent-applied surface of one of the remaining six inorganic members to which the second agent had been applied was bonded together with the first-agent-applied surface of the bonded structure 1. The first agent was then applied to the adhesive-free surface of the inorganic member of the bonded structure 1 to which the second agent had been applied. One minute after the start of application of the first agent to the bonded structure 1, the second-agent-applied surface of one of the remaining six inorganic members to which the second agent had been applied was bonded together and pressed together for 30 seconds to obtain a bonded structure 2 in which three inorganic members were bonded (Step 2). Step 2 was repeated five times in the same manner to obtain a bonded structure 3 in which all eight inorganic members were bonded. It took about 11 minutes from the start of application of the first agent to the time when all eight inorganic members were bonded to the bonded structure 1. The first and second agents were applied at room temperature (23°C). The resulting bonded structure 3 of each example was vibrated at 125 rpm for 1 minute, and then the presence or absence of peeling between the inorganic members in the bonded structure 3 was evaluated according to the following criteria. (standard) A (good): No peeling was observed between the inorganic members in the bonded structure. B (Poor): In the bonded structure, peeling was observed between the inorganic components, and misalignment occurred between the inorganic components.
[0072] [Table 1]
[0073] [Table 2]
[0074] Table 3
Claims
1. A two-part adhesive composition comprising: A method for producing a polymerization reaction system comprising: a radical polymerizable monomer (A); a polymerization initiator (B); and a reducing agent (C); the first agent contains the radical polymerizable monomer (A) and the polymerization initiator (B), the second agent contains the radical polymerizable monomer (A) and the reducing agent (C), An adhesive composition having a tensile shear strength T(1) of 0.01 MPa or more, as measured according to the following <Tensile Shear Strength>. <Tensile shear strength> A range of 20 mm from the end of a cold-rolled steel plate (JIS G 3141:2017, SPCC-SD) having a width of 25 mm, a length of 100 mm, and a thickness of 1.6 mm is sandblasted using alumina having a grain size of F150 at a processing pressure of 0.4 MPa and a gun / cold-rolled steel plate distance of 3 cm, and the surface of the sandblasted area is washed with acetone and then left to stand for 30 minutes at 23° C. to prepare two test pieces. Next, the first agent of the adhesive composition is applied to the sandblasted area of one of the test pieces to a thickness of 20 μm to prepare test piece 1, and the second agent is applied to the sandblasted area of the other test piece to a thickness of 20 μm to prepare test piece 2. Next, the test piece 1 and the test piece 2 are bonded together one minute after application of the first agent so that the bonded area is 25 mm × 12.5 mm, the bonded portion is clamped with two modern pinches, and the test piece 1 is fixed in a vice. Next, the modern pinches are removed 20 seconds after bonding, and 30 seconds after bonding, the test piece 2 is pulled at a tensile speed of 20 mm / min using a mechanical force gauge, and the value of the mechanical force gauge is read, and this value is the tensile shear strength T (1) (MPa).
2. Using a Brookfield viscometer, the temperature was 25°C and the shear rate was 0.6 s -1 2. The adhesive composition according to claim 1, wherein the viscosity of the first part and the second part is 30 mPa·s or more and 2000 mPa·s or less, as measured by a viscosity measuring method.
3. Using a Brookfield viscometer, the temperature was 25°C and the shear rate was 5.9 s -1 3. The adhesive composition according to claim 1, wherein the viscosity of the first part and the viscosity of the second part are each 20 mPa·s or more and 2000 mPa·s or less, as measured by a viscosity measuring method.
4. 3. The adhesive composition according to claim 1, which has a tensile shear strength T(60) of 0.01 MPa or more, as measured in accordance with the following <Tensile shear strength after standing for 60 minutes>. <Tensile shear strength after standing for 60 minutes> A range of 20 mm from the end of a cold-rolled steel plate (JIS G 3141:2017, SPCC-SD) having a width of 25 mm, a length of 100 mm, and a thickness of 1.6 mm is sandblasted using alumina having a grain size of F150 at a processing pressure of 0.4 MPa and a gun / cold-rolled steel plate distance of 3 cm, and the surface of the sandblasted area is washed with acetone and then left to stand for 30 minutes at 23° C. to prepare two test pieces. Next, the first agent of the adhesive composition is applied to the sandblasted area of one of the test pieces to a thickness of 20 μm to prepare test piece 1, and the second agent is applied to the sandblasted area of the other test piece to a thickness of 20 μm to prepare test piece 2. Next, 60 minutes after application of the first agent, the test piece 1 and the test piece 2 are bonded together so that the bonded area is 25 mm × 12.5 mm, the bonded portion is clamped with two modern pinches, and the test piece 1 is fixed in a vice. Next, 20 seconds after bonding, the modern pinches are removed, and 30 seconds after bonding, the test piece 2 is pulled at a tensile speed of 20 mm / min using a mechanical force gauge, and the value of the mechanical force gauge is read, and the value is taken as the tensile shear strength T (60) (MPa).
5. 3. The adhesive composition according to claim 1, wherein the tensile shear strength T(60) after standing for 60 minutes, measured according to the following <Lens shear strength>, divided by the tensile shear strength T(1) after standing for 1 minute, (T(60) / T(1)) is 0.5 or more and 1.5 or less. <Tensile shear strength> A range of 20 mm from the end of a cold-rolled steel plate (JIS G 3141:2017, SPCC-SD) having a width of 25 mm, a length of 100 mm, and a thickness of 1.6 mm was sandblasted using alumina having a grain size of F150 at a processing pressure of 0.4 MPa and a distance of 3 cm between the gun and the cold-rolled steel plate, and the surface of the sandblasted portion was washed with acetone and then left to stand for 30 minutes at 23° C. to prepare four test pieces. Next, the first agent of the adhesive composition was applied to the sandblasted areas of two of the test pieces to a thickness of 20 μm to prepare test piece 1, and the second agent was applied to the sandblasted areas of the remaining two test pieces to a thickness of 20 μm to prepare test piece 2. Next, one of the test pieces 1 and one of the test pieces 2 are bonded together 1 minute after application of the first agent so that the adhesive area is 25 mm x 12.5 mm, the adhesive portion is clamped with two modern pinches, and the test piece 1 is fixed in a vice. Next, the modern pinch is removed 20 seconds after bonding, and the value of the mechanical force gauge is read when the test piece 2 is pulled at a tensile speed of 20 mm / min 30 seconds after bonding, and the value is taken as the tensile shear strength T(1) (MPa). In addition, the other of the test pieces 1 and the other of the test pieces 2 are bonded together 60 minutes after application of the first agent so that the adhesive area is 25 mm x 12.5 mm, the adhesive portion is clamped with two modern pinches, and the test piece 1 is fixed in a vice. Next, 20 seconds after lamination, the modern pinch is removed, and 30 seconds after lamination, the test piece 2 is pulled at a tensile speed of 20 mm / min using a mechanical force gauge, and the value of the mechanical force gauge is read, and this value is the tensile shear strength T(60) (MPa).
6. The adhesive composition according to claim 1 or 2, wherein the radical polymerizable monomer (A) comprises a urethane (meth)acrylate and a polyfunctional (meth)acrylate.
7. The adhesive composition according to claim 1 or 2, wherein the radical polymerizable monomer (A) comprises a highly polar monomer.
8. The adhesive composition according to claim 1 or 2, further comprising an elastomer (D).
9. The adhesive composition according to claim 1 or 2, wherein the adhesive composition comprises a component having a structural unit derived from butadiene.
10. 3. The adhesive composition according to claim 1, wherein the content of the radical polymerizable monomer (A) is from 70% by mass to 99% by mass based on the total amount of the adhesive composition.
11. 3. The adhesive composition according to claim 1, wherein the content of the polymerization initiator (B) is 0.1 parts by mass or more and 20 parts by mass or less when the content of the radical polymerizable monomer (A) is 100 parts by mass.
12. 3. The adhesive composition according to claim 1, wherein the content of the reducing agent (C) is 0.01 parts by mass or more and 10 parts by mass or less when the content of the radical polymerizable monomer (A) is 100 parts by mass.
13. The adhesive composition according to claim 1 or 2, which is capable of bonding inorganic members to inorganic members.
14. An adhesive structure in which two or more inorganic members are adhered to each other, A bonded structure comprising the cured adhesive composition according to claim 1 between the inorganic members.
15. A method for producing a bonded structure, comprising the steps of: The adhesive composition is used to bond inorganic members to each other to obtain a bonded structure, The method for producing an adhesive structure, wherein the adhesive composition is the adhesive composition according to claim 1 or 2.
16. The bonding step includes: The method for manufacturing a bonded structure according to claim 15, further comprising a step of bonding a first agent-coated surface of the inorganic member to which the first agent has been coated and a second agent-coated surface of the inorganic member to which the second agent has been coated.
17. A method for producing a polymerization reaction system comprising: a radical polymerizable monomer (A); a polymerization initiator (B); and a reducing agent (C); A composition having a tensile shear strength T(1) of 0.01 MPa or more, as measured according to the following <Tensile Shear Strength>. <Tensile shear strength> A two-part adhesive composition is prepared, which comprises a first part containing a radical polymerizable monomer (A) and a polymerization initiator (B) and a second part containing the radical polymerizable monomer (A) and the reducing agent (C). A range of 20 mm from the end of a cold-rolled steel plate (JIS G 3141:2017, SPCC-SD) having a width of 25 mm, a length of 100 mm, and a thickness of 1.6 mm is sandblasted using alumina having a grain size of F150 at a processing pressure of 0.4 MPa and a distance of 3 cm between the gun and the cold-rolled steel plate, and the surface of the sandblasted portion is washed with acetone and then allowed to stand for 30 minutes at 23° C. Two test pieces are prepared as test pieces. Next, the first agent of the composition is applied to the sandblasted portion of one of the test pieces to a thickness of 20 μm to prepare test piece 1, and the second agent is applied to the sandblasted portion of the other test piece to a thickness of 20 μm to prepare test piece 2. Next, the test piece 1 and the test piece 2 are bonded together one minute after application of the first agent so that the bonded area is 25 mm × 12.5 mm, the bonded portion is clamped with two modern pinches, and the test piece 1 is fixed in a vice. Next, the modern pinches are removed 20 seconds after bonding, and 30 seconds after bonding, the test piece 2 is pulled at a tensile speed of 20 mm / min using a mechanical force gauge, and the value of the mechanical force gauge is read, and this value is the tensile shear strength T (1) (MPa).
Citation Information
Patent Citations
Acrylic curable resin composition
JP2018172565A
Two-agent type acrylic adhesive composition, and joined body that is joined together using the same
JP2020026507A
Adhesive set and method for producing structure
JP2021024910A